Enhancing Employee Job Satisfaction in the Tax Sector: the Role of Motivation and Hygiene Factors at the Directorate General of Taxes - Helmy Nurcahyo Wibowo; M. Farid Wajdi; Muhammad Sholahuddin (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to examine the influence of motivation and hygiene factors on employee job satisfaction at the Directorate General of Taxes. Utilizisng a survey method and a quantitative approach, this study collects and analyzes data to evaluate how these two factors contribute to job satisfaction. The findings indicate that both motivation and hygiene factors significantly positively impact job satisfaction within the Directorate General of Taxes. Employees experiencing high levels of work motivation tend to see an increase in their job satisfaction. This suggests that strong motivation from job aspects such as recognition, achievement, and responsibility can enhance employee job satisfaction. Similarly, hygiene factors such as good working conditions, supportive organizational policies, and positive interpersonal relationships at work also contribute to increased job satisfaction.The conclusions of this study underline the importance of paying attention to both motivation and hygiene factors as strategies to enhance employee job satisfaction. The Directorate General of Taxes is advised to implement policies and practices that support these aspects to improve employee well-being and overall organizational effectiveness. This research provides valuable insights for human resource management in designing and implementing programs that can strengthen work motivation and ensure adequate hygiene conditions in the workplace.